Hierarchical contribution of river–ocean connectivity, water chemistry, hydraulics, and substrate to the distribution of diadromous snails in Puerto Rican streams (2006)
ABSTRACT: Diadromous faunas dominate most tropical coastal streams and rivers, but the factors controlling their distribution are not well understood. Our study documents abiotic variables controlling the distribution and abundance of the diadromous snail Neritina virginea (Gastropoda:Neritidae) in the Caribbean island of Puerto Rico. An intensive survey of N. virginea density and shell size, and channel substrate, velocity, and depth was conducted at microhabitat, habitat, and reach scales of a coastal plain reach of the Rı´o Mameyes between August and December 2000. In addition, the inland extent of distribution (stream-network scale) and presence (regional scale) of N. virginea were surveyed in 32 coastal rivers around the island during summer 2001 and 2003. At the microhabitat scale, snail density and microhabitat electivity were greater in patches consisting of a mix of boulders and cobbles than in other types of substrate. At the habitat scale, snail density increased with depth. At the reach scale, snail density increased with fast and turbulent flows (riffle . pools . pond), whereas snail size showed the opposite pattern. At the regional scale, populations were present in 13 of 32 streams. Populations of N. virginea were not found in rivers that were disconnected from the ocean for most of the year because of channel dewatering, formation of sediment bars at their mouths, and low mean monthly discharge (Q¼0.69 m3/s). In contrast, rivers with N. virginea populations had a permanent (Q¼4.04 m3/s) or seasonal (Q¼2.88 m3/s) connection to the ocean over the year. At the regional scale, the inland distribution of populations was not correlated with stream gradient, but was negatively correlated with concentrations of SiO2, P, and acid neutralizing capacity of the water. Populations colonized montane reaches in only 5 rivers, all of which were forested and protected. Our study highlights the importance of taking a hierarchical approach in managing tropical coastal rivers, and the usefulness of neritid snails as biological indicators of the physical and chemical integrity of rivers.